Pengembangan E-Modul Interaktif Berbasis Google Sites untuk Mendukung Pembelajaran Blended Learning - Imam Mualim; Rudi HArtono; Imelia Puspita Sari; M. Herizal Habibi (Lembaga Pengembangan Kinerja Dosen, 2024)
This study aims to develop an interactive E-Module based on Google Sites as a learning medium to support the implementation of blended learning. The development process employed a Research and Development (R&D) model, consisting of several stages: needs analysis, design, product development, expert validation, limited trials, and revisions. The E-Module was designed to include learning materials, interactive videos, automatic quizzes, and user-friendly navigation accessible across various devices. Validation results from material experts and media experts indicated that the developed interactive E-Module falls into the “highly feasible” category, with only minor revisions required. Trials conducted with students showed that the E-Module successfully increased learning interest, facilitated better understanding of the material, and supported independent learning within the context of blended learning. Therefore, this Google Sites–based interactive E-Module is considered effective and practical as an alternative digital learning medium.